Penggunaan media sosial dan peran orang tua terhadap kejadian pernikahan dini - Asnuddin Asnuddin; Asrini Mattrah (Holistik Jurnal Kesehatan, 2020)
Social media use: The role of parents' perceptions about social media impact in early marriageBackground: Early marriage is a marriage that is conducted at adolescence, the factors causing early marriage are socio-cultural factors, economic pressure, level of education, difficulty in getting a job, social media, religion and views and beliefsPurpose: To find out the influence of social media and the role of parents on the incidence of early marriageMethod: A quantitative research using descriptive analytical research method with cross sectional study design with variable use of social media with the criteria for the results "active and inactive". For the variable of the role of parents with 2 outcome criteria, namely "influential and not influential". And for the variable incidence of early marriage, there are 2 criteria, namely age 14-16 years and age 17-19 years, the questionnaire used has been through the validity of previous researchers. Then the results of the data obtained were analyzed in the SPSS program using the Chi Square testResults: From the Chi Square test results for social media variables obtained p value = 0.001, then the value of p = 0.001 <0.05 (α) while the role of parents variable Chi Square test results obtained p value = 0.022, therefore the value of p = 0.022 <0.05 (α).Conclusion: Based on the results of the study it can be concluded that, there is a significant influence between the use of social media and the role of parents in the event of early marriage Keywords: Social media; Parents, Early marriagePendahuluan: Pernikahan usia dini adalah perkawinan yang dilakukan pada usia remaja, faktor penyebab pernikahan usia dini adalah faktor sosial budaya, desakan ekonomi, tingkat pendidikan, sulit mendapat pekerjaan, media sosial, agama serta pandangan dan kepercayaan.Tujuan: Untuk mengetahui pengaruh media sosial dan peran orang tua terhadap kejadian pernikahan dini di Kecamatan Marioriawa Kabupaten Soppeng Metode: Penelitian kuantitatif dengan menggunakan metode penelitian deskriptif analitik dengan rancangan cross sectional study dengan variabel penggunaan media sosial dengan kriteria hasil “aktif dan tidak aktif”. Untuk variabel peran orang tua dengan 2 kriteria hasil yaitu “berpengaruh dan tidak berpengaruh”. Dan untuk variabel kejadian pernikahan dini ada 2 kriteria  yaitu umur 14-16 tahun dan umur 17-19 tahun,  kuesioner yang di gunakan sudah melalui uji validitas peneliti sebelumnya. Kemudian hasil data yang di dapatkan dianalisis di program SPSS dengan menggunakan uji Chi SquareHasil: Dari hasil uji Chi Square untuk variabel media sosial didapatkan nilai p=0,001, maka nilai p=0.001<0.05 (α) sedangkan variabel peran orang tua hasil uji Chi Square didapatkan nilai p=0,022, oleh karena itu nilai p=0.022<0.05 (α).Simpulan: Berdasarkan hasil penelitian dapat di simpulkan bahwa, Ada pengaruh yang signifikan antara penggunaan media sosial dan peran orang tua terhadap kejadian pernikahan dini